Analysis of the Effect of Weight Loss on Eustachian Tube Function by Transnasal Videoendoscopy. Issue 3 (15th May 2022) - Eravci, Fakih Cihat; Yildiz, Bariş Doğu; Özcan, Kürşat Murat; Moran, Münevver; Çolak, Mustafa; Karakuş, Mehmet Fatih; Karakurt, Süleyman Emre; Ikinciogullari, Aykut; Dere, Haci Hüseyin
Abstract : Objective: To investigate the effect of weight loss after bariatric surgery on eustachian tube (ET) function with video endoscopy. Materials and Methods: The present study was conducted as a prospective cohort and was completed with 19 patients. Three-step tympanometry (basal, Toynbee, Valsalva), dynamic slow-motion video endoscopy, and the Eustachian Tube Dysfunction Questionnaire-7 (ETDA-7) were applied to the patients preoperatively before bariatric surgery and in the postoperative 6th month. Dynamic slow-motion video endoscopy was graded between 0 and 3, or classified as patulous, as indicated in the literature. Results: The mean body mass index of 6 male and 13 female patients decreased from 47.3 ± 4.6 to 31.2 ± 5.4. Grade decline (median 2 ± 1) was experienced in all patients in DSVE, and 1 patient resulted as patulous ET. The ETDA-7 scores decreased in11 patients, remained stable in 7 patients, and increased in 1 patient with patulous ET. The statistical analysis of the preoperative and postoperative DSVE grading and ETDA-7 scores, excluding the patulous ET patient, was found to be significant ( P   =  0.001 and P   =  0.003, respectively). There was no significant change in any of the tympanometry parameters ( P  > 0.05). Conclusions: Rapid weight loss with bariatric surgery results in an improvement in both the DSVE images and in the complaints of ET dysfunction in the majority of patients, but in some patients it may result in patulous ET. Therefore, preoperative evaluation of the ET with DSVE and questioning the patient's complaints are important in predicting patients who may develop patulous ET.